The Audit tax deductions in recovery of value added tax in special contributors. Case MATERIALS, C. A. (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
This research aims to establish the foundations of the documentation process in recovering Withholding Value Added Tax (VAT) through a tax audit. The field study, based descriptive documentary. Legal instruments were used: Tax Code, Tax Law, Administrative Order 056. The population is the Company Materials, CA, designated Special Taxpayer and VAT withholding agent. The sample consists of (4) administrative workers involved in Tax Withholding. The applied questionnaire consists of twenty 28 items with closed questions. We evaluated the procedure for the recovery of tax withholdings. Evaluation and verification of formal tax obligations and duties is based on tax audit procedures, the application and development of the respective tax audit program of value added tax, provides evidence of planning and scope thereof, serving as instructions for the completion of the assignment.
Keywords: value added tax; recovery of deductions; tax audit; special contributors